Tunable‐Sized Polymeric Micelles and Their Assembly for the Preparation of Large Mesoporous Platinum Nanoparticles. Issue 34 (21st July 2016) - Jiang, Bo; Li, Cuiling; Tang, Jing; Takei, Toshiaki; Kim, Jung Ho; Ide, Yusuke; Henzie, Joel; Tominaka, Satoshi; Yamauchi, Yusuke
Abstract: Platinum nanoparticles with continuously tunable mesoporous structures were prepared by a simple, one‐step polymeric approach. By virtue of their large pore size, these structures have a high surface area that is accessible to reagents. In the synthetic method, variation of the solvent composition plays an essential role in the systematic control of pore size and particle shape. The mesoporous Pt catalyst exhibited superior electrocatalytic activity for the methanol oxidation reaction compared to commercially available Pt catalysts. This polymeric‐micelle approach provides an additional design concept for the creation of next generation of metallic catalysts. Abstract : Dancing to a different tune : Platinum nanoparticles with continuously tunable mesoporous structures were prepared by a one‐step approach based on polymeric micelles. Their particle and pore sizes were controlled by altering the solvent composition (see picture). By virtue of their high surface area, these mesoporous Pt structures were more efficient electrocatalysts for methanol oxidation than commercially available Pt catalysts.